The using of digital technologies in the design of the developing educational environment of the university - Исалиева, Сауле; Момбек, Алия; Улдахан, Шынгыс (Pedagogy and Psychology, 2020)
The article raises the problem of introducing digital and distance technologies in the scientific and educational process, as well as issues of developing digital literacy and competence of teachers. The authors made an attempt to highlight various digital education projects implemented in Kazakhstan, provide examples of various scientific seminars and webinars on the training of pedagogical personnel, foreign researches in this area, analyze the impact of online learning on the organization, content and teaching methods. As an illustration of the blended learning strategy, the experience of the annual international competition of scientific research of schoolchildren and students “Zhas zertteushi” in online format is highlighted. The article describes the main provisions of the competition, the algorithm and organization of the competition using distance technologies based on synchronous learning. The authors note the distinctive features of the scientific event and conclude that constant feedback and the readiness of the competition moderators to provide methodological assistance creates a stable motivation for the participants to research activities.